1991
DOI: 10.1002/nur.4770140105
|View full text |Cite
|
Sign up to set email alerts
|

Early postpartum transition: Progress in maternal identity and role attainment

Abstract: Sets of early postpartum transition variables and relationships among them examined in this study were: (a) Maternal attributes (parity, age, education); (b) infant feeding plan (extent of breast-feeding); (c) birthing conditions (supports and stressors during labor and delivery); (d) birthing experience (how well labor and delivery went, usefulness of postpartum learning resources, adequacy of hospital stay); and (e) transition markers (evaluation of parenting and of infant- and self-care capability). Infant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
2
28
2
Order By: Relevance
“…Our study is the first, to our knowledge, where this has been observed, even if this was not significant in the multiple linear regression analysis. Higher parental age and educational level have been associated with lower maternal satisfaction,24 25 but were not significant here; this has also been observed elsewhere 17 22…”
Section: Discussionsupporting
confidence: 52%
“…Our study is the first, to our knowledge, where this has been observed, even if this was not significant in the multiple linear regression analysis. Higher parental age and educational level have been associated with lower maternal satisfaction,24 25 but were not significant here; this has also been observed elsewhere 17 22…”
Section: Discussionsupporting
confidence: 52%
“…Although the literature is inconsistent regarding this predictor, the current finding has been reported (Pridham et al, 1991;Secco, 2002). At both times, multiparity was a strong predictor of parenting self-efficacy.…”
Section: Discussioncontrasting
confidence: 49%
“…For example, some researchers have reported that maternal age does not affect parenting self-efficacy (Mercer, 1986;Pridham, Lytton, Chang, & Rutledge, 1991), whereas Conrad, Gross, Fogg, and Ruchala (1992) found a positive correlation between age and maternal confidence. There are inconsistencies in findings, which may be accounted for by differences in construct definition, methodologies, timing of measurements, and tools.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is reported that adolescent mothers show less responsive and sensitive behaviors, use fewer vocalizations, and provide a less stimulating environment for their infants than adult mothers (Mercer, 1995) and do not typically exhibit the same variety or frequency of interactions as adult mothers (Martell, 2001). These differences are important because the maternal-infant relationship is reflected in the interactive behaviors of both mother and infant, which comprise a critical measure that further defines parenting (Pridham & Chang, 1985, 1989Pridham, Lytton, Chang, & Rutledge, 1991). Adolescents are also less cognitively prepared to engage in newborn care, experience more stress in parenting, and are less adaptive in their parenting style when compared with adult mothers (Gee & Rhodes, 2003;Mercer, 2004).…”
mentioning
confidence: 99%